2010
DOI: 10.1016/j.bbmt.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Race and Outcomes of Autologous Hematopoietic Cell Transplantation for Multiple Myeloma

Abstract: Blacks are twice as likely to develop and die from multiple myeloma (MM) and are less likely to receive an autologous hematopoietic-cell transplant (AHCT) for MM compared to whites. The influence of race on outcomes of AHCT for MM is not well described. We compared the probability of overall survival, progression-free survival, disease progression and non-relapse mortality among black (N=303) and white (N=1892) recipients of AHCT for MM, who were reported to the Center for International Blood and Marrow Transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 25 publications
(20 reference statements)
8
41
1
Order By: Relevance
“…Our data confirm the data from transplant series [29] that show the prognosis of African American and Caucasian patients with MM is comparable if access to care is equal. We were able to add to these findings that, in an academic center with equal access to care, the outcome of MM in all patients is equal regardless of race.…”
Section: Discussionsupporting
confidence: 81%
“…Our data confirm the data from transplant series [29] that show the prognosis of African American and Caucasian patients with MM is comparable if access to care is equal. We were able to add to these findings that, in an academic center with equal access to care, the outcome of MM in all patients is equal regardless of race.…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that blacks may not have had the same access to new therapies as whites, consistent with previous reports that blacks are 50% less likely than whites to undergo ASCT, 46 while other studies have reported blacks and whites to have similar outcomes with ASCT. 18,19 Likewise, a SEER Medicare-based study found that among MM patients Ն 65 years of age, blacks were less likely than whites to receive chemotherapy. 47 Based on small numbers, we attempted to separately assess changes in survival after the introduction of ASCT and novel drugs.…”
Section: Discussionmentioning
confidence: 99%
“…17 A recent study of 91 patients receiving ASCT in an equal access health system observed no difference in survival by race 18 a registry study by the Center for International Bone Marrow Transplantation confirmed this finding. 19 Four population-based studies [20][21][22][23] have demonstrated improved survival in MM after the advent of novel therapies such as ASCT (1994), [24][25][26] immunomodulatory drugs (IMiDs; 1999), 27-30 and bortezomib (2003). 31,32 None of these studies assessed the impact of new treatments on survival by race.…”
Section: Introductionmentioning
confidence: 99%
“…2 5 The reasons for all of these differences are not clear, but taken together they suggest underlying biological differences between MM tumors in AA and EA patients. Baker and colleagues sought to answer whether different genomic alterations between AA and EA with MM could account for these clinical observations.…”
mentioning
confidence: 99%
“…Physiological mechanisms for regulation of ADP-mediated platelet activation also exist, among which are the activities of ecto-nucleotidases that hydrolyze ADP (and ATP) to AMP and adenosine. [5][6][7] CD39 is one such ecto-nucleotidase. CD39 is normally expressed on the surfaces of endothelial cells in the vasculature, where it helps to keep platelets from becoming activated in the presence of an intact endothelium.…”
mentioning
confidence: 99%